Uji Residu Pupuk Kandang Sapi dan Jarak Tanam Sorgum (Sorghum bicolor L.) terhadap Pertumbuhan dan Hasil Tanaman Kacang Tanah (Arachis hypogeae L.) dalam Tumpangsari - Alfianus Haumein (Fakultas Pertanian, Universitas Timor, 2020)
Research to determine the effect and interaction test of cow cage fertilizer residues and spacing of sorghum (sorghum bicolor l.) in intercropping with peanuts (arachis hypogeae l.) on growth and yields of sorghum and peanuts. The research was carried out in July to October 2019 in the experimental garden of the Faculty of Agriculture, University of Timor, Kelurahan Sasi, Kota Kefamenanu District, TTU Regency, using a 4 x 3 factorial Randomized Block Design (RBD) plus sorghum monoculture plots and peanuts namely: the first factor dosing residue of cow manure: Without fertilizer, the dose of fertilizer 10 t/ha, the dose of fertilizer 20 t/ha, the dose of fertilizer 30 t/ha, the second factor planting spacing: Spacing 20 cm x 70 cm, planting spacing 30 cm x 70 cm, Plant spacing of 40 cm x 70 cm. Each treatment combination was repeated 3 times so that there were 52 research units. The results showed that there was no interaction between cow manure residue and plant spacing on all observation parameters. The treatment of cow manure residue showed significantly different from the control on all growth parameters and yield parameters with dry seed yield per hectare given by cow manure residue 30 t/ha. Spacing treatment showed that there was no significant difference at all treatment levels except for the weight parameter of planting seeds, 20 cm x 70 cm spacing resulted in the heaviest bean seeds.